Perception et acquisition du figement lexical en langue maternelle - Sułkowska, Monika (Neophilologica, 2016)
The main objective of this paper is to discuss the issue of perception, comprehension and well acquired phraseological structures that are perceived as idiomatic expressions. First, the author will investigate a spectrum of methods used in perception of idiomatic meanings. Then, the author will present the results of a wide range of research and analysis in the field of phraseological units and their acquisition.